Association Between Familial Hypercholesterolemia and Risk of Cardiovascular Events and Death in Different Cohorts: A Meta-Analysis of 1.1 Million Subjects - Yu, Yani; Chen, Lei; Zhang, Honghong; Fu, Zihao; Liu, Qi; Zhao, Haijing; Liu, Yuqi; Chen, Yundai (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims The association of familial hypercholesterolemia (FH) with risk of cardiovascular events (CVE) and death in different cohorts is controversial. We aimed to assess the risk of CVE and death in patients with FH in different cohorts, including CHD and ACS patients, White and Asian, different diagnostic criteria. Methods We searched PubMed, MEDLINE, and Web of Science electronic databases through May 2021 to identify cohort studies of CVE and death in patients with FH. Results We found 18 eligible studies with 1,139,788 participants, including 34,261 patients. There were 31,287 ACS patients, of whom 2,338 were combined with FH. Randomized-effects meta-analysis showed that in patients with FH, relative risk (RR) of CVE and death was 1.87 (95% CI 1.21–2.88), among which CVE was 2.14 (95%CI 1.26–3.64), all-cause of death RR = 1.12 (95% CI 0.89–1.41), and cardiac death RR = 1.03 (95% CI 0.59–1.79). Risk of CVE and death in general population with FH was 2.85 (95% CI 0.72–11.21), hyperlipidemia population RR = 1.59 (95% CI 1.05–2.41), coronary heart disease patients (CHD) RR = 1.46 (95% CI 1.24–1.72), and acute coronary syndrome patients (ACS) RR = 1.71 (95% CI 1.19–2.46). Among ACS patients, the RR of CVE in patients with FH was 1.91 (95% CI 1.55–2.35), the RR of all-cause of death was 1.03 (95% CI 0.80–1.32), and the RR of cardiac death was 1.03 (95% CI 0.59–1.79). The risk of CVE and death in ACS patients with FH in White was 1.69 (95% CI 1.09–2.64) and Asian 1.90 (95% CI 1.31–2.75). RR in patients with Dutch Lipid Network criteria (DLCN) ≥6 vs. <3 points was higher (RR = 2.24, 95% CI 1.69–2.97). RR for long-term follow-up was 1.68 (95% CI 1.09–2.61) and for short-term follow-up was 1.80 (95% CI 1.16–2.78). The results of the overall population were similar, but RR for overall population during a short-term follow-up was 1.49 (95% CI 0.81–2.73). We followed PRISMA checklist to complete meta-analysis. Conclusions The risk of CVE and death was increased in patients with CHD, especially in patients with ACS. DLCN ≥ 6 points was suggested for clinical diagnosis of FH. The risk of long-term and short-term CVE and death increased in ACS patients with FH. Registration Number INPLASY2021110010.